Dexmedetomidine Protects Against Kidney Fibrosis in Diabetic Mice by Targeting miR-101-3p-Mediated EndMT - Li Song; Songlin Feng; Hao Yu; Sen Shi (SAGE Publishing, 2022)
Objective: Our main purpose is to explore the effect and mechanism of Dexmedetomidine (DEX)  in diabetic nephropathy fibrosis. Methods: Diabetic model was established by intraperitoneal injection of streptozotocin (STZ) treated CD-1 mice and high glucose cultured human dermal microvascular endothelial cells (HMVECs). Immunofluorescence was used to detect renal endothelial-mesenchymal transition (EndMT); Hematoxylin and Eosin (HE) staining and Masson's Trichrome Staining (MTS) was used to analyze renal fibrosis; CCK-8 was used to evaluate cell viability; Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) was used to assess the expression of miR-101-3p; Western blots were utilized to judge the protein expression levels of EndMT, extracellular matrix and TGF-β1/Smad3 signal pathway. Results:  In this study, we first found that the protective effect of DEX on DN was related to EndMT. DEX alleviated kidney fibrosis by inhibiting EndMT in diabetic CD-1 mice. DEX could also inhibit high glucose-induced HMVECs EndMT. Then, we confirmed that miR-101-3p was the regulatory target of DEX. The expression of miR-101-3p was decreased in diabetic CD-1 mice and high glucose-induced HMVECs. After DEX treatment, the miR-101-3p increased, and the inhibition of miR-101-3p could counteract the protective effect of DEX and aggravate the EndMT. Finally, we found that the TGF- β1/Smad3 signal pathway was involved in the protective effect of DEX on DN. DEX inhibited the activation of TGF-β1/Smad3 signal pathway. On the contrary, inhibiting miR-101-3p promoted the expression of TGF-β1/Smad3. Conclusion: DEX protects kidney fibrosis in diabetic mice by targeting miR-101-3p-mediated EndMT.